The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1989
DOI: 10.1016/0014-2999(89)90634-1
|View full text |Cite
|
Sign up to set email alerts
|

Affinity profiles of hexahydro-sila-difenidol analogues at muscarinic receptor subtypes

Abstract: In an attempt to assess the structural requirements of hexahydro-sila-difenidol for potency and selectivity, a series of analogues modified in the amino group and the phenyl ring were investigated for their affinity to muscarinic M 1 -(rabbit vas deferens), Mr (guinea-pig atria) and Mr (guinea-pig ileum) receptors. All compounds were competitive antagonists in the three tissues. Their affinities to the three muscarinic receptor subtypes differed by more than two orders of magnitude and the observed receptor se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(38 citation statements)
references
References 28 publications
7
31
0
Order By: Relevance
“…This is in agreement with previous data indicating direct M 3 receptormediated intestinal smooth muscle contraction (Eglen et al, 1994). The rank order of potency of telenzepine on muscarinic receptors is M 1 4M 3 4M 2 (Eltze et al, 1993;Waelbroeck, 1992), and for p-F-HHSiD it is M 3 4M 1 4M 2 (Lambrecht et al, 1989). The chosen dose of telenzepine in this study has earlier been shown to successfully inhibit M 1 receptordependent nerve-induced NO-formation from intestinal tissue, without a ecting the M 3 receptor-dependent contractile response (Iversen et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in agreement with previous data indicating direct M 3 receptormediated intestinal smooth muscle contraction (Eglen et al, 1994). The rank order of potency of telenzepine on muscarinic receptors is M 1 4M 3 4M 2 (Eltze et al, 1993;Waelbroeck, 1992), and for p-F-HHSiD it is M 3 4M 1 4M 2 (Lambrecht et al, 1989). The chosen dose of telenzepine in this study has earlier been shown to successfully inhibit M 1 receptordependent nerve-induced NO-formation from intestinal tissue, without a ecting the M 3 receptor-dependent contractile response (Iversen et al, 1997).…”
Section: Discussionsupporting
confidence: 92%
“…In the presence of the selective muscarinic M 3 receptor antagonist p-F-HHSiD (Lambrecht et al, 1989) at 3610 77 M, the McN-A-343 (10 75 M)-induced relaxations were signi®-cantly enhanced to 38+4% of maximal relaxation (n=9, P50.05) (Figures 3 and 4). In addition, the increase in smooth muscle tone following the relaxation was inhibited by 82+10% by p-F-HHSiD at 3610 77 M, P50.001) ( Figure 3 The selective muscarinic M 1 receptor antagonist telenzepine (Eltze et al, 1985;Schudt et al, 1988) …”
Section: Resultsmentioning
confidence: 97%
“…In Table 2, pA2 values for these antagonists determined in other studies in various preparations and shown in reviews by Hulme et al (1990) and by Caulfield (1993) and in an article by Lambrecht et al (1989) are also presented for comparison. It is clear that the pA2 values for these antagonists against pilocarpine-induced relaxation are close to those for M3 antagonism in other studies.…”
Section: Effects Of Muscarinic Antagonistsmentioning
confidence: 99%
“…In the published literature, atropine has been used as a non-selective high affinity antagonist at muscarinic receptors. Pirenzepine is a relatively high affinity antagonist for Ml muscarinic receptors with intermediate affinity for M4 muscarinic receptors and lower affinity for the M2 and M3 muscarinic receptors (Lambrecht et al, 1989;Caulfield & Brown, 1991;Dorje et al, 1991;Grimm et al, 1994). (11-[[[2 -(diethylamino)methyl] -l-piperidinyl]acetyl] -5,1 1-dihydro-6H-pyridol [2,3,-b][1,4]benzodiazepine-6-one) has high affinity for the M2 muscarinic receptor, but also has affinity for the Ml muscarinic receptor with lower affinity for the M3 and M4 muscarinic receptors (Birdsall & Hulme, 1983;Giachetti et al, 1986;Hammer et al, 1986).…”
Section: Introductionmentioning
confidence: 99%
“…4-DAMP has a relatively high affinity for M3 muscarinic receptors but also has affinity at Ml and M4 muscarinic receptor subtypes (Dodds et al, 1987;Eltze & Figala, 1988;Eltze et al, 1993;Grimm et al, 1994). HHSiD and p-F-HHSiD have a relatively higher affinity for M3 muscarinic receptors than M2 muscarinic receptors but do have affinity for Ml and M4 muscarinic receptors (Lambrecht et al, 1989;Waelbroeck et al, 1990). Himbacine has relatively high affinity for M2 and M4 muscarinic receptors with lower affinity for Ml and M3 muscarinic receptors (Eglen et al, 1988;Caulfield & Brown, 1991;Miller et al, 1992;Russo et al, 1993).…”
Section: Introductionmentioning
confidence: 99%